By using elimination method the solution for the given equations 5x+6y=17 and -10x-9y= -43 are x=7 and y= -3.
Explanation:
The given equations are,
..................................(1)
..............................(2)
Step:1
By elimination method,
Multiplying the equation (1) by 9 ( Eqn (1) × 9)
.................................(3)
Multiplying the equation (2) by -6 ( Eqn (2) × -6)
................................(4)
Step:2
Subtracting the Equations (3) and (4),
![45x+54y=153](https://img.qammunity.org/2021/formulas/mathematics/middle-school/jenhb3up7qq28am7z4iiys8xbzdca4vr0g.png)
![60x+54y=258](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ghlslko0qt4pxe473lwn8cb9zzsqxnv7am.png)
( - )
(
) + (
) = (
)
(
) = (
)
![x = 7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/haui06dyzu06cccqprdnwfvnybjm6zc7di.png)
Step:3
Substitute the x=7 in equation (1),
( 5 × 7 ) + (
) = 17
= -18
= -3
Step:4
Check for solution,
Substitute the x and y values in Eqn (1),
![5x+6y=17](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3zpi3v5kj3w3gqhbngbtw23dslhylykcs8.png)
( 5 × 7 ) + ( 6 × -3 ) = 17
( 35 ) - ( 18 ) = 17
17 = 17
Result:
The solution for the equations 5x+6y=17 and -10x-9y= -43 are x=7 and y= -3.